STRATEGI KOMUNIKASI DALAM PROGRAM REHABILITASI NARKOBA DI KOTA PEKANBARU (Studi Dalam Institusi Penerima Wajib Lapor Yayasan Satu Bumi) - Balqis Adillah Putri; MUhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted with a qualitative approach. The number of resource persons as many as 11 people with the method of collecting purposive and accidental sampling. Data collection techniques by means of interviews, observation, and documentation of rehabilitation activities carried out by the One Earth Foundation IPWL. All data are then analyzed qualitatively and are triangulated to describe the Communication Strategy in the rehabilitation program as seen from the Iriantara Strategic Communication model, namely, Communicators, Communicators, Messages, Audiences, and Responses from the program. The results showed that the strategy of the One Bumi Foundation IPWL communicator was seen from the credibility of the communicators, had high knowledge, and had a sense of caring about social problems. The target audience of this program is abusers and drug addicts by making RBM. The message strategy given is in the form of general messages, counseling messages, messages in the form of motivation, education, persuasion, information, and religion, and home visit messages. The media strategy used is in the form of group media, visual media, and online media. The response obtained from the One Earth Foundation IPWL rehabilitation program is likely to be positive. and online media. The response obtained from the One Earth Foundation IPWL rehabilitation program is likely to be positive. and online media. The response obtained from the One Earth Foundation IPWL rehabilitation program is likely to be positive. Keywords: Rehabilitation, Communication Strategy, IPWL Satu Bumi Foundation